2010
DOI: 10.1029/2009gl042154
|View full text |Cite
|
Sign up to set email alerts
|

Amazon forests did not green‐up during the 2005 drought

Abstract: [1] The sensitivity of Amazon rainforests to dry-season droughts is still poorly understood, with reports of enhanced tree mortality and forest fires on one hand, and excessive forest greening on the other. Here, we report that the previous results of large-scale greening of the Amazon, obtained from an earlier version of satellitederived vegetation greenness data -Collection 4 (C4) Enhanced Vegetation Index (EVI), are irreproducible, with both this earlier version as well as the improved, current version (C5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
291
1
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(313 citation statements)
references
References 26 publications
15
291
1
6
Order By: Relevance
“…However, the magnitude and location of the sink of CO2 show large uncertainties [5,6], which lead to continuous researches focusing on monitoring vegetation activity change in the middle and high latitudes of the Northern Hemisphere. There are many investigations about the interannual variation in vegetation activity over the middle and high latitudes of the Northern Hemisphere based on the satellite-derived long-term records of Normalized Difference Vegetation Index (NDVI) data sets [7][8][9][10][11]. The vegetation activity in the northern middle and high latitudes demonstrated a consistent increasing trend according to the studies with the Global Inventory Monitoring and Modeling Studies (GIMMS) group produced NDVI data sets during 1981-1991 [12] and 1981-1999 [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the magnitude and location of the sink of CO2 show large uncertainties [5,6], which lead to continuous researches focusing on monitoring vegetation activity change in the middle and high latitudes of the Northern Hemisphere. There are many investigations about the interannual variation in vegetation activity over the middle and high latitudes of the Northern Hemisphere based on the satellite-derived long-term records of Normalized Difference Vegetation Index (NDVI) data sets [7][8][9][10][11]. The vegetation activity in the northern middle and high latitudes demonstrated a consistent increasing trend according to the studies with the Global Inventory Monitoring and Modeling Studies (GIMMS) group produced NDVI data sets during 1981-1991 [12] and 1981-1999 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Data from conventional optical sensors suggested inconclusive results. One study showed the greening of the forest (increase in vegetation index) due to higher active radiation (less clouds) during the early stages of drought [14], while others proposed either browning of the forest from water stress [15], or greening in later stages of drought from opening of the canopy from potential tree mortality [16]. Satellite optical observations over tropical forests are impacted by clouds and atmospheric aerosol, causing noise in surface reflectance data [15].…”
Section: Introductionmentioning
confidence: 99%
“…One study showed the greening of the forest (increase in vegetation index) due to higher active radiation (less clouds) during the early stages of drought [14], while others proposed either browning of the forest from water stress [15], or greening in later stages of drought from opening of the canopy from potential tree mortality [16]. Satellite optical observations over tropical forests are impacted by clouds and atmospheric aerosol, causing noise in surface reflectance data [15]. The first cloud and smoke-free observation of the impacts of recent droughts on the forests of Amazonia was captured by time-series measurements of the satellite microwave scatterometer (QuickSCAT, QSCAT) [17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Keller et al (2004) showed that the interplay between the wet and dry seasons relative to CO 2 uptake/efflux varied across the Amazon Basin. On coarser spatial scales enhanced uptake coincident with drought has been documented using remote sensing (Huete et al, 2006;Saleska et al, 2007) but this result is disputed due to data artifacts (Samanta et al, 2010). The overall ambiguity in response is confounded by sparse monitoring networks in the tropics and large interannual variability (Bosquet et al, 2000) relative to a small source magnitude with large uncertainties (Gurney et al, 2002;Stephens et al, 2007).…”
Section: Introductionmentioning
confidence: 99%